Kesesuaian Lokasi Lahan Sawah Dilindungi (LSD) terhadap Rencana Tata Ruang Wilayah (RTRW) Kabupaten Bojonegoro - Rozak, Achmad Miftahur (Jurnal Litbang: Media Informasi Penelitian, Pengembangan dan IPTEK, 2025)
ENGLISHBojonegoro Regency, as the third largest contributor to rice production in East Java, is at risk of agricultural land conversion due to population growth which triggers an increase in the need for built-up land. To control this, 93,054.38 ha of Protected Paddy Fields (LSD) have been established. This control is also realised through the establishment of Sustainable Food Agriculture Area (KP2B) of 43,201.7 ha in Regional Regulation Number 5 of 2021 concerning the Regional Spatial Plan (RTRW) of Bojonegoro Regency 2021-2041, with a food crop area reaching 77,757 ha. This research aims to determine the suitability of LSD designation with the RTRW. The assessment of the level of conformity used a quantitative method with a spatial overlay analysis approach. It was found that 66,280.97 ha of LSD were in conformity with the RTRW, while 26,542.98 were not. The suitability of LSD with agricultural land includes the availability of irrigation network, productivity and planting index of 48,093.5 ha. There are 11,447.98 ha of food crop areas outside LSD that have the potential to become reserve land. These results can serve as an illustration for local governments in proposing changes to LSD designations to align with existing conditions and spatial planning. INDONESIAKabupaten Bojonegoro sebagai penyumbang produksi padi terbesar ketiga di Jawa Timur, terdapat resiko alih fungsi lahan pertanian akibat pertumbuhan penduduk yang memicu peningkatan kebutuhan lahan terbangun. Untuk mengendalikan hal tersebut telah ditetapkan Lahan Sawah Dilindungi (LSD) seluas 93.054,38 Ha. Pengendalian tersebut juga diwujudkan melalui penetapan Kawasan Pertanian Pangan Berkelanjutan (KP2B) seluas 43.201,7 ha dalam Perda Nomor 5 Tahun 2021 tentang Rencana Tata Ruang Wilayah (RTRW) Kabupaten Bojonegoro 2021–2041, dengan luas kawasan tanaman pangan mencapai 77.757 ha. Penelitian ini bertujuan mengetahui kesesuaian penetapan LSD dengan RTRW. Penilaian tingkat kesesuaian tersebut menggunakan metode kuantitatif dengan pendekatan analisis spasial overlay (tumpang susun). Didapatkan kesesuaian LSD dengan RTRW seluas 66.280,97 ha, sedangkan 26.542,98 tidak sesuai. Kesesuaian LSD dengan lahan pertanian mencakup ketersediaan jaringan irigasi, produktivitas dan indeks penanaman seluas 48.093,5 ha. Terdapat 11.447,98 ha kawasan tanaman pangan di luar LSD yang berpotensi menjadi lahan cadangan. Hasil ini dapat menjadi gambaran Pemerintah daerah dalam mengusulkan perubahan penetapan LSD agar selaras dengan kondisi eksisting dan perencanaan tata ruang.